Civic wars : democracy and public life in the American city during the nineteenth century - Ryan, Mary P. (University of California Press, 1997)
The near extinction of civic life in American cities has been proclaimed for many years. Today, multiculturalism and political correctness are deemed the villains. Yet in the nineteenth century, at the apex of public processions, ceremonies, and civic celebrations, American cities were arguably as full of cultural differences and as fractured by social and economic changes as any metropolis today. To investigate how their citizens formed an integral public culture despite their heterogeneity, Mary Ryan, an award-winning scholar of the nineteenth century, began her research for this book. Quite unexpectedly, she found not harmonious communities but nearly incessant civic conflict which, she argues, erupted into full-scale municipal warfare even before the onset of the War between the States. Locating her study in New York, New Orleans, and San Francisco, Ryan analyzes these conflicts on spatial, ceremonial, and political planes. The story begins in 1825 with an account of how the residents of antebellum cities created a democratic political culture out of multifarious differences. It quickly turns to the trials, failures, and reversals of the democratic experiment that characterized the 1850s and 1860s. When the Civil War ended in 1865, Ryan demonstrates, the people of these cities recast their differences as bolder division, especially those of race and gender, and sometimes class as well. In the end, Ryan reclaims this tumultuous urban history as the durable crucible of democracy. Through her graceful and powerful narrative of the fate of public life in the last century, she discovers the foundations of America's resilient democratic culture.